The reception of Gulhermina Suggia's concerts in Spain (Revista Argentina de Musicología, 2023)
Guilhermina Suggia (1885-1950) is the image of a woman who broke with the traditional model of femininity: she occupied a space in public life, developed an intellectual and artistic work with which she broke into the cultural sphere consecrated to patriarchy, she traveled, she changed residence, city and even country and remained single by choice for much of her life; in short, an autonomous person. Based on the musical discourses published in the press, Guilhermina Suggia's concert tour in Spain will be reconstructed as well as her reception in a country where a minority of women shared her degree of professional and personal emancipation and where music critic was a largely masculinized profession.
Keywords: Guilhermina Suggia; Pau Casals; music critic; musical associations